COMPOSITION OF PURIFIED ANTHOCYANIN ISOLATED FROM TEAK AND IT’S IN VITRO ANTIOXIDANT ACTIVITY - Murukan, Greeshma; K., Murugan (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present study evaluates purification, characterization of anthocyanin from in vitro culture of teak and its antioxidant potential. Methods: Anthocyanin was extracted from in vitro culture, purified by using amber lite XAD column and fractionated by Liquid chromatography mass spectrometry (LC-MS/MS). Various antioxidant assays were carried such as 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), 2,2'-azino-bis-3-ethyl-benzothiazoline-6-sulphonic acid (ABTS), Oxygen radical absorbance capacity (ORAC), Nitric oxide (NO) and Hydrogen peroxide (H2O2). Results: Liquid chromatography mass spectrometry (LC-MS/MS) revealed the major fraction as cyanidin 3-(2-xylosyl-rutinoside) with unknown peaks. The amount of anthocyanin was 15.23 mg/g monomeric anthocyanin. Further, the potential antioxidant capacity of the teak anthocyanin was comparable to common vegetables and fruits. Similarly, high correlations of anthocyanin with antioxidant activity, such as oxygen radical absorbance capacity (ORAC), 2,2'-azino-bis-3-ethyl-benzothiazoline-6-sulphonic acid (ABTS), and 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) (r = 0.95, 0.93, and 0.80) were found. Conclusion: The high anthocyanins content and potential antioxidant activity suggests that teak anthocyanin may be applied in the food industry as a good source of natural pigments